(untitled) (Global Journal of Science Frontier Research, 2019)
Botanicals have gained prominence as alternate to most artificial pesticides within the management of mosquitoes. Insecticides derived from botanical sources are natural products, are chiefly secondary metabolites and natural chemicals that have some advantages over their conventional counterparts in that they are highly degradable. In the present study, the phytoextracts of Nicotiana tabacum leaves was tested for larvicidal activity against the third in star larvae of the dengue vector, Aedes aegypti at concentrations of 0.0125, 0.025, 0.05 and 0.1% for 24, 48 and 72 hours of exposure. The petroleum ether extract exhibited the highest activity with respective LC50 values of 0.09, 0.03 and 0.01%. Nicotiana tabacum leaf extracts for the control of mosquito larva is well documented as many types of research have gone into the larvicidal activity of tobacco plant extracts for the control of vector mosquitoes, and the mode and mechanism of action of the phytochemical component nicotine responsible for the mortality of mosquito larvae is highlighted.